Profil Proses Berpikir Siswa Dalam Menyelesaikan Soal-Soal Pythagoras Ditinjau Dari Gaya Belajar Dan Gaya Kognitif - Nurlastyaningtyas, Maya; , Rita Pramujiyanti KhotimahS.Si, M.Sc (2016)
This research aimed to describe the profile thinking process of students in solving pythagoras problems in terms of learning styles and cognitive styles. This type of research is qualitative descriptive design phenomenology. The respondents were students of class VIII E on Junior High School state Margorejo 1. The technique of data collection through questionnaires method, tests, interviews, and documentation. The technique of data analysis used data reduction, data presentation, and conclusion. The data validity use methodology triangulasm which integrate testing, interviews, and documentation. The results showed that students in class VIII E Junior High School 1 Margorejo in solving pythagoras terms of learning styles of visual, auditory, kinesthetic and cognitive style field dependent and field independent uses of the different thought process. Students type of visual - field dependent and type of auditory - field dependent using semi-conceptual thinking process. Students type of visual - field independent, type of auditory - field independent, type of kinesthetic - field dependent, and type of kinesthetic - field independent using conceptual thinking process. Keywords: cognitive styles, learning styles, the thinking process.